Efektivitas Manajemen Pembiayaan Sekolah Unit Pelaksana Teknis Daerah Satuan Pendidikan Formal Sekolah Dasar Negeri Mandupang - Rusman, Rusman; Pratiwi, Sri Nurbaidah; Isman, Muhammad (UMSU, 2024)
The aim of the research is to determine the effectiveness of education financing management in improving the quality of education. The type of research approach is a mixed method approach. This research was carried out by the Mandumpang state elementary school UPTD. Using observation, interview, documentation and questionnaire data collection techniques. Data analysis techniques by presenting data, displaying data and drawing conclusions. The respondents for this research were school principals, deputy principals, teachers, treasurers and committee members as well as students. The research results show that Educational Financing Planning at UPD SPF Mandumpang State Elementary School includes the Development of Educators and Education Personnel, Calculation of Educator Development Cost Allocations, and Implementation of Educator Development Cost Allocations. Implementation of Education Financing at Mandumpang State Elementary School Uptd Spf by controlling the budget in the school must be controlled by the school principal as school manager. as well as preparing reports on the results of program implementation to related parties. The effectiveness of education financing management at the UPTD SPF SDN Mandumpang State Elementary School with the principle of openness in managing financing at the UPTD SPF SDN Mandumpang State Elementary School, is highly emphasized by the school principal and all those involved. The trend level for school financing management effectiveness is with a mean value of 78.11% and a median of 79.00% so that school financing management in the UPTD SPF SDN Mandumpang State Elementary School has an impact.